Cytokine profle during occult hepatitis B virus infection in chronic hepatitis C patients - Ribeiro, Camilla Rodrigues de Almeida (2021)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Virologia Molecular. Rio de Janeiro, RJ, Brasil.